Naḥwa Manhaj Wasatī Fī Al-Tafsīr: Min Al-Wasaṭiyya Ilā Al-Muwāṭana Fī Miḥwar Al-Insāniyya ʿinda Al-Ḥabīb ʿalī Al-Jufrī - Muhammad Makmun; Avif Alfiyah (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2024)
This article aims to explore the concept of Islamic moderation and its role in achieving citizenship through the principle of "humanity before religiosity" from the perspective of Habib Ali Zain al-Abidin al-jufri. The study addresses the following research questions: How does Ḥabīb ʿAlī al-Jufrī promote the concept of "humanity before religiosity," and how does this concept contribute to enhancing Islamic moderation and achieving citizenship? The article employs a critical analytical methodology to study the texts and interpretations of Habib Ali Zain al-Abidin al-Jufri, focusing on his interpretations that emphasize human values over strict adherence to religious laws. The study concludes that the principle of "humanity before religiosity" proposed by Ḥabīb ʿAlī al-Jufrī aligns with the core values of humanity and the objectives of Islamic law (Sharia). Ḥabīb ʿAlī al-Jufrī considers humanity as the foundation of moderation, which is the path to achieving citizenship in contemporary society. The research illustrates that the essence of moderation lies in prioritizing human values over religiosity, thereby promoting peaceful coexistence and tolerance among individuals and groups. The article asserts that moderation, as interpreted by Ḥabīb ʿAlī al-Jufrī, is an effective factor in affirming and achieving citizenship amidst religious, ethnic, and political diversity within the context of the nation-state. Achieving citizenship is linked to achieving humanity, where individuals enjoy the freedom of mature choice, including the freedom to choose citizenship. Accordingly, the article highlights the importance of moderation in Islamic interpretation as a means to enhance human values and citizenship, offering new insights into the relationship between religion and citizenship in contemporary societies.